The 7B-1 mutation in tomato (Solanum lycopersicum L.) confers a blue light-specific lower sensitivity to coronatine, a toxin produced by Pseudomonas syringae pv. tomato - Bergougnoux, Véronique; Hlavácková, Vladimíra; Plotzová, Renáta; Novák, Ondrej; Fellner, Martin (Journal of experimental botany, 2009)
The spontaneous mutant 7B-1 in tomato (Solanum lycopersicum=Lycopersicon esculentum) is a photoperiod-dependent male-sterile mutant previously reported as resistant to various abiotic stresses specifically under blue light. Since this finding improved the potential of 7B-1's use in breeding programmes, its susceptibility to stress induced by coronatine (COR), the phytotoxine produced by several Pseudomonas syringae strains, was assessed in this study. The 7B-1 mutant was found to be less sensitive than the corresponding wild type (WT) to COR treatment in a blue light-dependent manner. Treatment of WT and 7B-1 plants with COR induced a strong accumulation of salicylic acid (SA), jasmonic acid (JA), and abscisic acid (ABA) in hypocotyls. Interestingly, accumulation of ABA and SA in the 7B-1 mutant was distinctly greater than in WT, especially in blue light. Based on the cross-talk between SA- and JA-signalling pathways, expression analysis of NPR1 and COI1 genes, respectively involved in these pathways, was investigated in COR-stressed plants. The blue light-specific lower sensitivity of 7B-1 plants to COR was found to be associated with blue light-specific overexpression of the NPR1 gene. These data suggest that the SA-dependent NPR1-dependent pathway could be involved in the lower sensitivity of the 7B-1 mutant to COR. The role of anthocyanins and ABA accumulation during the response to COR is also discussed in the present study.
Keywords: Solanum lycopersicum; indeny; Plant Leaves; Cyclopentanes; světlo; Pseudomonas syringae; Plant Diseases; Models, Biological; mutace; polymerázová řetězová reakce s reverzní transkripcí; anthokyaniny; Reverse Transcriptase Polymerase Chain Reaction; regulace genové exprese u rostlin; listy rostlin; cyklopentany; Gene Expression Regulation, Plant; aminokyseliny; Light; Amino Acids; Abscisic Acid; oxylipiny; Oxylipins; rostlinné proteiny; Anthocyanins; Bacterial Toxins; nemoci rostlin; biologické modely; Plant Proteins; kyselina abscisová; bakteriální toxiny; Mutation; Indenes